Force and energy characteristics in competitive slalom - Reid, R.; Gilgien, M.; Haugen, O.; Kipp, R.; Smith, G. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The external forces acting on a skier in alpine skiing include gravitational, air drag, and snow reaction forces. A skier controls trajectory and speed primarily through regulating the ski's interaction with the snow and, thereby, controlling the size and orientation of the snow reaction force. The purpose of this investigation was to gain further insight into skier technique through examining the magnitude and timing of the external forces acting under competitive conditions and to describe the relative contributions of each external force towards skier mechanical energy changes.